Research Utilizing the Global Mobile Network of Huawei Telecom to Examine and Project Deployment - MA BINCHANG, MA BINCHANG; NIZAMUDDIN INAMDAR, DR MOHAMMAD NIZAMUDDIN INAMDAR (International Journal of Multidisciplinary Research and Studies, 2024)
This is why "This master's thesis aims to demonstrate the processes by which criteria are "born" as standards, including the identification, categorization, and implementation of these processes. The initiative is also motivated by a desire to make a useful contribution to business and industry by shedding light on the complexities of the standardization process, in this case as it pertains to mobile communications. There will be significant advancements over the current 4G services in the next generation of mobile technology, including faster speeds, lower latency, more devices, and new capabilities like Machine to Machine communication, Device to Device communication (D2D), and Internet of Things architecture [17]. It is crucial for networking experts and developers to examine how the ITU establishes specifications that are then followed by telecommunications corporations because doing so will help them better understand the development of mobile communications and the various standards that have accompanied it. The fifth generation of wireless networks (5G) has already been deployed and tested in the wild. The improvements enable a stable connection 14 times better than the current 4G, as shown by tests conducted by telecom carriers and manufacturers of 5G equipment [18]. Smartphone makers are starting to provide 5G-capable devices, and this trend will continue over the next several years. After all the hype around 5G and increased data transfer rates, it's time to examine how the new standard stacks up against older ones, as well as how various implementations and solutions compare to the IMT-2020 standard. There is also a shortage of data on how the main telecom firms participate in standard-setting and what sort of effect they have "on advancement. Therefore, it is necessary to assess the level of development made by each company in the field of 5G [19].